PENGARUH PERTUMBUHAN EKONOMI, BELANJA BANTUAN SOSIAL, DAN BELANJA PENDIDIKAN TERHADAP KEMISKINAN - Rossa, Amelya; Fajri Ananda, Candra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
High economic growth and increased spending on social assistance and education spending still causes relatively high levels of poverty in the Districts/Cities of East Java Province in 2013-2022. Therefore, the aim of this research is to analyze and determine the influence of economic growth, social assistance spending, and education spending on poverty in the Districts/Cities of East Java Province. The type of data used is panel data from 38 districts/cities for ten years using the panel data regression analysis method. The research results show that social assistance spending has a negative and significant effect on poverty, education spending has a negative and significant effect on poverty, and economic growth has a positive and significant effect on poverty. This is because the capital-intensive sector is growing more rapidly than the labor-intensive sector. So, the government needs to make efforts to increase employment-based sectors and be able to absorb more workers, especially in capital-intensive sectors which make a greater contribution to economic growth in the districts/cities of East Java Province.